Genealogy of Light: Charismatic Leadership and Religious Authority in Alevism - Çiçek, Hüseyin I. (Interdisciplinary journal for religion and transformation in contemporary society, 2025)
Charisma plays an important role in every society. In certain cases, the sources for this are of the same origin (transcendental or worldly). Charismatic leaders and people enjoy the trust of their members and can determine norms and values. This article starts from the Weberian definition of charisma and aims to find out to what extent it is transferable to the Alevi Dede.